Experience of registration of reflection of radio signals from plasma meteor tracks in the observatory of SKSU - Sartin, S.A.; Solodovnik, A.A.; Useinov, B.M.; Zhukeshov, A.M.; Amrenova, A.U. (Recent Contributions to Physics, 2020)
One of the actual problems of astrophysical studies of The solar system bodies is the registration of meteor phenomena occurring in the upper layers of The earth’s atmosphere. Statistics of such events allow to obtain averaged estimates of the concentration of meteoroids in near-earth space. These data have an important practical application on the security of space infrastructure development. In this paper, it is shown that optical methods of meteor registration, despite their diversity, suffer from limitations associated with the influence of atmospheric meteorology, daylight and anthropogenic illumination of the sky. In this regard, the transition to the use of methods of registration of meteors based on the property of formed or plasma tracks to reflect radio waves is relevant. The results of work on the development of the material base and methods of radio observations of meteors in the center of astrophysical research of North Kazakhstan state University are presented. The approach of registration of the radio signal reflected from the plasma meteor track of the remote station is applied. Information processing was carried out online using standard software. Comparison of the obtained results with the published data on the application of the method showed a high degree of similarity of the amplitude-time structure of the signal with typical for the applied method. The daily frequency distribution of meteor events is also quite realistic. Thus, we can state the creation in the Republic of Kazakhstan of the first point for registration of meteors in the radio range.